Environmental correlates of internal coloration in frogs vary throughout space and lineages - Franco-Belussi, Lilian [UNESP]; Provete, Diogo Borges; De Oliveira, Classius [UNESP] (Wiley, 2017)
Internal organs of ectotherms have melanin-containing cells that confer different degrees of coloration to them. Previous experimental studies analyzed their developmental origin, role in immunity, and hormonal regulation. For example, melanin increases with ultraviolet radiation (UV) and temperature in frogs and fish. However, little is known about how environmental variables influence the amount of coloration on organs among amphibian species over a large spatial extent. Here, we tested how climatic variables (temperature, UV, and photoperiod) influence the coloration of internal organs of anurans. We recorded the level of melanin pigmentation using four categories on 12 internal organs and structures of 388 specimens from 43 species belonging to six anuran families. Then, we tested which climatic variables had the highest covariation with the pigmentation on each organ after controlling for spatial autocorrelation in climatic variables and phylogenetic signal in organ coloration using the extended version of the RLQ ordination. Coloration in all organs was correlated with the phylogeny. However, the coloration of different organs was affected by different variables. Specifically, the coloration of the heart, kidneys, and rectum of hylids, Rhinella schneideri, some Leptodactylus, and Proceratophrys strongly covaried with temperature and photoperiod, whereas that of the testicle, lumbar parietal peritoneum, lungs, and mesenterium of Leiuperinae, Hylodidae, Adenomera, and most Leptodactylus had highest covariation with UV-B and temperature. Our results support the notion that melanin pigmentation on the surface of organs of amphibians has an adaptive function conferred by the protective functions of the pigment. But most importantly, internal melanin seems to respond differently to climatic variables depending on the lineage and locality in which species occur.
Keywords: anurans; internal melanin; photoperiod; temperature; UV-B